Menjembatani Barat Dan Timur: Implementasi Prinsip Ham Universal Dalam Yuriprudensi Islam Kontemporer - Anggraeni, Meri; Ardiansyah, Ahmad; Sa'adah, Maura Rofiqoh; Sudrajat, Shinta Azzahra (JUSTITIABLE - Jurnal Hukum, 2025)
The intersection between universal Human Rights (HAM) and Islamic law hasbeen an interesting topic of discussion in recent decades. Human Rights (HAM)were declared in 1948 by the United Nations (UN) General Assembly. HumanRights have become a reference for the international world and influence allaspects of contemporary international relations and law. However, theinterpretation and application of human rights in the national scope are not assmooth as their acceptance. The clash between local culture and law withuniversal human rights is often unavoidable. Islamic law is a product of IslamicSharia which is officially implemented in almost all Muslim countries which arealso members of the UN. Is there a clash between international human rights law and Islamic law and how to resolve it? This paper aims to bridge the gap betweenthese two systems by analyzing the implementation of human rights principles incontemporary Islamic jurisprudence. Despite differences in historicaldevelopment and sources of authority, both human rights and Islamic law havethe same goal, namely to protect human dignity and basic rights. This study willexamine the similarities in values, differences in interpretation, and efforts thathave been made to harmonize these two systems. In addition, this paper will alsoidentify the challenges faced in the harmonization process, and recommend somerecommendations for the future.